Quality Evaluation of Postgraduate Programs from the Perspective of Students (Faculty of Education, Imam Abdulrahman Bin Faisal University (IAU), KSA) - AL-Mekhlafi, Mohammed Sarhan (Journal of Education in Black Sea Region, 2020)
This study is an attempt to determine the implementation level of quality standards in graduate programs at the college of Education, IAU in the light of the National Center for Academic Accreditation and Evaluation standards from the viewpoints of students. Data were collected from a randomly selected sample of 86 graduate students. To achieve the study goals, respondents were requested to answer a five-point scale questionnaire comprised of 69 items related to eight quality standards. The result shows an average degree of overall implementation. At the standards level, findings revealed a higher average for implementing quality standards related to teaching staff and quality learning. On the other hand, lower averages of implementation were found for the quality standards of Scientific Research and Projects, Students, Learning Resources, Facilities and Equipment, Curricula, Mission and Goals, and Graduate Qualities and Learning Outcomes. A statistically significant difference (P< 0.05) was found between males and females on the teaching staff standard favoring female students and non-significant differences were found on the implementation of quality standards according to their graduate specialization. The study concluded with recommendations directed for decision makers and higher administration to monitor the implementation of quality assurance within graduate programs.